Association of Candida sp. with the Degrees of Dysplasia and Oral Cancer: A Study by Calcofluor White under Fluorescent Microscopy - Sandhya Tamgadge; Avinash Tamgadge; Aswathy Pillai; Mayura Chande; Siddharth Acharya; Narayan Kamat (Iranian Society of Pathology, 2017)
Background and objective:Candida albicans (C. albicans) play a significant role in oral mucosal carcinogenesis. It can be identified using various techniques in cytological smears. But, very few studies have been conducted on histopathological sections using calcofluor white M2R under fluorescent microscopy. Additionally, detection and quantification of Candida colonies and its correlation with various grades of oral leukoplakia and oral carcinomas have not been explored much. Methods:The current retrospective study included 80 samples from archives consisting of 60 samples in the study group (10 cases each of mild, moderate, and severe epithelial dysplasia (totally 30) and 30 cases of oral carcinoma). Sections were stained with calcofluor white (CFW) and 10% KOH for the observation under fluorescent microscopy and correlated with different grades of oral leukoplakia and oral carcinomas. Chi-square test was used in SSPS software to study the presence and absence of Candida sp. in different groups. Results:The study groups of oral carcinoma and dysplasia showed a significant association with Candida sp. (P=0). When carcinoma was compared with each grade of dysplasia, except mild dysplasia (P=4.4E-05), both moderate (P=0.402195) and severe dysplasia (P=0.558746) showed an insignificant P-value. When the groups of mild (13.3%), moderate (30%), and severe (33.3%) dysplasia were considered independently, the incidence of Candida sp. increased as the grade of dysplasia increased. The number of colonies have been counted and the maximum number of colonies have been observed in carcinoma and the least have been observed in mild dysplasia. Conclusion: A significant association of Candida colonies with epithelial dysplasia and oral cancer was established. Further, CFW was found a promising candidate to identify Candida colonies in tissue sections using fluorescent microscopy.